Kandungan Unsur Hara Kompos Eceng Gondok yang Dikomposkan dengan Berbagai Macam PGPR - Nurul Istiqomah; Farida Adriani; Nina Rodina (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2018)
Material compost can be foliage, rice husk, organic garbage, and herbs water hyacinth that considered to be weeds because the population is a huge and speed growing fast. To make use of herbs water hyacinth as compost can by using PGPR that serves as decomposer to accelerate decay. PGPR contained the bacterium Pseudomonas fluorescent and Bacillus polymixa. The material used a source of PGPR, namely root bamboo, roots daughter shame, roots cane, and roots bulrush. The research aims to understand the influence of the nutrient content water hyacinth (Eichornia crassiper (Mart.)) in composted with different kinds of PGPR (roots bamboo, roots bulrush, roots daughter shame, and roots cane). The research in Kandang Jaya Village District of Lampihong Balangan Regency of February to the month of April 2016. The research using design random complete (RAL) single factor. Factors the treatment is types of material PGPR (P) as four the economic situation of PGPR bamboo roots (p1), PGPR bulrush roots (p2), PGPR Mimosa pudica roots (p3) and PGPR cane roots (p4) as 250 ml/decomposer. The research results show that the various from of PGPR is not had a real impact on the nutrient content N-total, P and K as well as the value of the C-organic on composting results c.